Parenteral formulation of nanoemulsion loaded with chloramphenicol for meningitis treatment - Musa, Siti Hajar (2014)
Meningitis is a disease caused by the inflammation of the brain due to bacterial infection. The most common causative agent in bacterial meningitis is Streptococcus pneumonia. The bacterial infection occurs in the brain which is protected by a barrier known as blood-brain barrier (BBB). This barrier consists of a very selective membrane which only allows small particle with lipophilic characteristic to pass through. In the current medication treatment,third generation cephalosporin has been used widely in treating this disease. However, this family of drug (cephalosporin) is no longer effective towards the meningitis bacteria due to the drug resistance problem. Traditional antibiotic such as chloramphenicol has caught medical community’s attention back to overcome the problem. Delivery of chloramphenicol could be improved via nanoemulsion system with nano-size droplet range. From the solubility study, it was found that palm kernel oil esters (PKOEs) and safflower seed oil (1:1 ratio) was the best combination in solubilizing chloramphenicol compared to other oil mixture. Lecithin was best mixed with Tween 80 as co-surfactant in the emulsion system, resulting in smaller particle size (131.5 nm) and low polydispersity index (0.135) reading. Methods of emulsification such as spontaneous method (stirring process),spontaneous with high shear homogenizer, spontaneous with ultrasound homogenizer and spontaneous with high pressure homogenizer were studied. With respect to the particle size and polydispersity index, combination of spontaneous method with high pressure homogenizer gave the best particle size and polydispersity index which was 70.65 nm and 0.154, respectively. Response Surface Methodology (RSM) was used as a tool in optimization process. Relation between independent variables (oil, lecithin and glycerol amount) and response variables (particle size, zeta potential and osmolality) were analysed. From three dimension (3D) analysis models, it was observed that particle size, zeta potential and osmolality value of nanoemulsion was largely influenced by the amount of oil, lecithin and glycerol, respectively. RSM has suggested composition with 4% oil, 2.50% lecithin and 2.25% glycerol which resulted with nanoemulsion system with 95.33 nm of particle size, 0.238 of polydispersity index, -36.91 mV of zeta potential and 200 mOsm/kg of osmolality. These actual values show good agreement with the predicted values; 86.96 nm (particle size), 0.234 (polydispersity index), -33.47 mV (zeta potential), 198 mOsm/kg (osmolality). Dosage optimization showed that stable nano-antibiotic emulsion system was successfully achieved up to 3 mg/ml of chloramphenicol. Three formulations with varied loading dosage (1, 2 and 3 mg/ml) were found to be stable at 4ºC. Transmission Electron Microscopy (TEM) of negatively stained nanoemulsion showed that the oil droplets were in a spherical shape and uniform in size. Toxicity analysis shows that nanoemulsion entrapment has successfully reduced the toxicity effect of chloramphenicol towards 3T3 cells. In-vitro study showed a good penetration of chloramphenicol through the cellulose acetate membrane which resulted a zero order release mechanism. Stability evaluation based on the particle size for three months showed that the particle size remain in a nano-size with less than 5% of size changes. Emulsion entrapment study shows no chloramphenicol leakage from the oil droplet. Drug assay through 3 months of storage showed a consistent drug loading in the emulsion with less than 10% of drug lost. In conclusion, the nanoemulsion formulation is a promising vehicle for the delivery of chloramphenicol parenterally (intravenous route).